Severe Abdominal Manifestations in Juvenile Dermatomyositis. Issue 2 (February 2020) - Besnard, Caroline; Gitiaux, Cyril; Girard, Muriel; Galmiche-Rolland, Louise; Talbotec, Cécile; Quartier, Pierre; Bodemer, Christine; Berteloot, Laureline; Bader-Meunier, Brigitte
Abstract : ABSTRACT: Juvenile dermatomyositis (JDM) is a rare and heterogeneous pediatric-onset idiopathic inflammatory myopathy. Gastrointestinal (GI) involvement occurs in 22% to 37% of JDM patients but has only been described in case reports. In this retrospective, single-center, observational study, we aimed to assess the causes and management of severe GI manifestations in JDM patients. We studied a cohort of 9 patients among 110 JDM patients followed during the study period (8.3%). The GI complications were related to JDM in most cases (17/19), with digestive tract involvement (n = 10), acute pancreatitis (n = 4), and hepatitis (n = 3). Three patients died from refractory JDM 2.9 years (2–3.6) after the JDM diagnosis. We highlight the need to consider pancreatitis as a main diagnostic factor in JDM patients with severe GI manifestations and the requirement of early aggressive treatment for these patients.